Manajemen Strategis Lembaga Dakwah Kampus Al-Izzah UINSU dalam Membentuk Generasi Dakwah Milenial - Syarbaini, Syarbaini; Hasibuan, Wildan Ansori; Nasution, Wina Warohmah; Dalimunthe, Yaqub (Ahsan: Jurnal Dakwah dan Komunikasi, 2024)
This research aims to analyze the strategic management implemented by the Al-Izzah Campus Da'wah Institute (LDK) at the North Sumatra State Islamic University (UINSU) in forming the millennial preaching generation. The millennial generation has unique characteristics, such as being adaptive to technology, tends to be creative, and is active on social media, so a strategic da'wah approach is really needed. The research method used is descriptive qualitative with a case study approach. Data collection was carried out through in-depth interviews, participant observation and document analysis. The research subjects consisted of LDK Al-Izzah administrators, active members, and students involved in da'wah programs. The research results show that LDK Al-Izzah implements three main stages in strategic management: (1) Planning, through preparing a technology-based vision, mission and da'wah program; (2) Implementation, by utilizing social media, inter-organizational collaboration, and competency-based training; and (3) Evaluation, through regular assessments of program success and its impact on member development. This strategy has proven effective in increasing student participation and creating a millennial generation who is able to preach creatively and relevantly to the challenges of the times. It is hoped that this research can become a reference for other campus Da'wah institutions in developing adaptive and innovative da'wah strategies, as well as supporting the role of campuses as centers for the format ion of future generations of da'wah.